Achieving the Sustainable Development Goals (SDGs): between the role of Islamic social finance and financial inclusion - Mahadi, Nur Farhah; Mohd. Zain, Nor Razinah; Muhammad Ahmad, Shamsuddeen (2020)
The purpose of this study is to analyse the role of Islamic social finance and financial inclusion in achieving eight of the seventeen goals of sustainable development goals (SDGs) which is SDG1, SDG2, SDG3, SDG5, SDG8, SDG9, SDG10, and SDG17 in the 2030 agenda for SDGs, as propagated by United Nations Member States in 2015. Then, a critical analysis is made to explain the possible contribution of Islamic social finance and financial inclusion in realizing the SDGs which brings balanced to the physical, emotional, mental and spiritual of the community in supporting overall economic growth. Further research and empirical studies can be conducted to examine the relationship between Islamic social finance, financial inclusion, and SDGs which is aligned with Maqᾱṣid al-Sharῑ῾ah. The results may also motivate the financial industries to promote Islamic social finance products and corporate social responsibilities as well as enhance the development of Islamic social finance and financial inclusion in attaining SDGs which soon will provide significant social impacts as the results will enable new initiatives by industries and policy makers to develop Islamic social finance and financial inclusion to achieve SDGs which is seen as being parallel with Maqᾱṣid al-Sharῑ῾ah.